336. Validation of a methodology for SPECT/CT absolute quantification. (December 2018) - Ferrando, O.; Chimenz, A.; Ciarmiello, A.; Foppiano, F.
Abstract : Purpose: To evaluate the activity quantification performance of our SPECT/CT scanner (SYMBIA T2 – SIEMENS) and to verify a methodology for absolute activity quantification. Methods: Quantitative SPECT/CT studies can be performed using the methodology proposed by Zeintl et al.[1] . The instrumentation consists of an uniform cylindrical phantom (5680 mL) and an IEC NEMA torso-phantom with hot sphere inserts. 99m Tc was used to prepare the radioactive solutions. Different sphere-to-background ratio (RSB ) were used (61:1, 44:1, 33:1, 10:1). Images were reconstructed using the proprietary OSEM 3D algorithm with resolution recovery (FLASH 3D, Siemens Healthcare), CT-based attenuation correction and energy window-based scatter correction. A system calibration factor (S) relating the count rate ( cps ) and the activity ( mCi ) contained in a tridimensional volume was determined together with the activity recovery coefficients. The phantom results were extended to 99mTc-MAA patient acquisitions for activity quantification in liver lesions. Lesions contouring was performed using the Volumetric Analysis Software (Siemens Healthcare). Results: A calibration factor of 17190 cps/mCi was obtained for 99m Tc. Recovery coefficients (Fig. 1) vary from 90% (for volumes ⩾25 mL) to 20% (for volumes up to 0.5 mL). For 128 updates and no post-smoothing filtering we obtain the maximum activity recovery (about 90%) for a volume ⩾25 mL. Hot sphere contrast and activity quantification improve with higher updates while the sphere to background ratio and the background variability increase. A balance between activity recovery and background variability is obtained with 8 iterations, 8subset and no filtering. Applying the phantom results to 7 MAA-99mTc acquisitions, activity accumulated in liver lesions can be determined with an accuracy ⩽10% (Table 1). Conclusions: With the proposed methodology spect activity quantification can be reached with an accuracy ⩽10% for 99m Tc acquisitions. In the future the method will be tested also with other isotopes used in the clinical practice.